PEMANFAATAN BUILDING INFORMATION MODELING (BIM) UNTUK PEMBANGUNAN AS-BUILT DRAWING 3D PADA BANGUNAN LIGHT RAIL TRANSIT (LRT) (STUDI KASUS : STASIUN LRT CINDE, PALEMBANG) - Riky T Kurniawan, Aries
Building Information Modeling (BIM) can be defined as a representation of the physical and functional aspects of a building through the utilization of communication and information technology. The advantages of the information presentation of the BIM model can be utilized in the manufacturing of as-built drawing documentation. As-built drawing is a description of the actual form of a building that has been through the construction process, and can be utilized in the monitoring operations and management of a facility or building. Commonly as-built drawing is used as a 2D asbuilt drawing. 3D as-built drawing is required in order to provide more complete information for the management and monitoring operations of a building. A case study on this study was conducted on the building of a Light Rail Transit (LRT) station in Cinde Palembang. The collection of research data is done by collecting the LRT Cinde Palembang Station 3D point clouds data from the result of the measurement using Terrestrial Laser Scanner from other research. Data point processing of 3D point clouds data into BIM models include the stage of determining the building part is modeled, identifying the building part of the 3D data point clouds, and the creation of the BIM model with the scan-to-BIM and parametric modeling methods. Presentation of 3D as-built drawing is done by displaying the dimension information and adjusting the view of the BIM model created and creating the layout with the Manual Image Information Standard 2015. The analysis done is BIM utilization benefit analysis for the creation of 3D as-built drawing by doing the identification of the advantage of the BIM making process for as-built drawing 3D. The results of the research obtained are BIM models made with the scan-to-BIM and parametric modeling methods from 3D point clouds data can be used to model and provide location information, shape, and part dimensions of the building, so it can be utilized for the creation of as-built drawing 3D. The process of creating 3d as-built drawing with BIM can be done by collecting 3D clouds data points, making BIM model using scan-to-BIM and parametric modeling method, and serving as-built drawing 3D with the Manual image information standard document 2015. Parametric modeling methods and family model creation in BIM generation can accelerate the modeling process